Impact of perfusate concentration on hyperthermic intraperitoneal chemotherapy efficacy and toxicity in a rodent model - Liesenfeld, Lukas; Hillebrecht, Christian; Klose, Johannes; Schmidt, Thomas; Schneider, Martin (Journal of surgical research, 2020)
Background - Cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to be beneficial in treating limited peritoneal carcinomatosis (PC) from colorectal cancer (CRC). Perfusate volume directly affects treatment concentration and therefore is a key parameter defining HIPEC; yet little is known about the impact of perfusate concentration on systemic toxicity and treatment morbidity. - Materials and methods - PC was induced through intraperitoneal injection of human CRC cell lines. A novel perfusion model was developed to treat athymic nude mice with continuous circulation of adequately miniaturized volumes of heated perfusate. Oxaliplatin HIPEC was performed applying different volumes of perfusate with fixed doses or fixed concentrations. Early postoperative mortality and morbidity were assessed as well as long-term survival. In addition, antiproliferative and proapoptotic effects of HIPEC were determined in vitro and in vivo. - Results - Perfusate concentration crucially affected the toxicity of fixed-dose oxaliplatin HIPEC as indicated by postoperative weight loss and early postoperative mortality. Applying different perfusate volumes at a fixed concentration did not influence toxicity. Adequately miniaturized HIPEC with oxaliplatin did not exert relevant cytotoxic effects toward PC arising from human CRC cells in vivo. - Conclusions - We describe a novel murine model that adequately miniaturizes all physical parameters of HIPEC as applied in humans. HIPEC drug concentration is a crucial parameter determining excess toxicity and should be better standardized. HIPEC with oxaliplatin fails to induce relevant antitumor activity or to improve survival in this murine model of PC from CRC.
Gesehen am 25.08.2020